Cervical cancer screening - Ade, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A cervical cancer is one of the most common cancers among the women in many developing countries. It is estimated that around 83% of all the new cases of cervical cancer and 85% of all the deaths occur in the developing countries. Cervical cancer is the commonest malignancy among women in India. The cervical cancer contributes around 12% of all types of cancers among the women.